Students’ Perceptions of the English Day Program as A Speaking Skill Booster - Zakiyah, Irhamna Latifata; Siahaan, Leroy Holman; Sari, Tiara Dian (CV. Ulil Albab Corp, 2025)
This study explores Grade 7 students’ perceptions of the planned implementation of the English Day Program at MTs Attaqwa 17 as an effort to enhance their English speaking skills. The program aims to encourage students to use English in daily school interactions. Employing a qualitative case study design, data were collected through open-ended questionnaires, semi-structured interviews, and classroom observations. The findings indicate that students generally have positive perceptions of the program, believing it could improve their confidence and fluency in speaking. Nevertheless, challenges such as fear of making mistakes, limited vocabulary mastery, and speaking anxiety were identified. Students suggested incorporating enjoyable and supportive activities, such as games, peer partnerships, and teacher encouragement, to increase engagement. The study concludes that successful implementation of the English Day Program requires a gradual, student-centered approach supported by teachers and the school environment.